Expression of fibroblast growth factor-2 after application of the Queen's crepe-myrtle leaf (Lagerstroemia speciosa) and aloe vera extract gel in the wound healing process of hyperglycemic - Razi, Fachrul; Hardianto, Andri; Riawan, Lucky; Priosoeryanto, Bambang Pontjo (Universitas Padjadjaran, 2021)
Introduction: Fibroblast Growth Factor-2 (FGF-2) have a role in stimulating the proliferation and migration of various types of cells in the wound healing process. Hyperglycemic conditions can disrupt the wound healing process. Lagerstroemia speciosa are known to have antyphyerglycemic and antioxidant effects. Aloe vera is a plant that has been used for long time in topical treatment of wounds.This study was aimed to analyse the FGF-2 after application of Queen's crepe-myrtle leaf (Lagerstroemia speciosa) and aloe vera extracts gel in the wound healing process of hyperglycemia. Methods: A pure experimental study was conducted with simple random sampling. The sample was 27 experimental animals (CI 95%; power test 80%) of Sprague Dawley rat induced to have a hyperglycemic state using alloxan and had their palate injured. The immunohistochemical examination was performed to assess FGF-2 expression level. Samples were divided into three groups with a simple random sampling technique: nine of the rats received the Lagerstroemia speciosa extract gel application; nine rats received the aloe vera extract gel application on the injured palate; another nine rats in the control group. Examination of the FGF-2 expression level was performed on the third, seventh, and fourteenth observation days. Results: Overall, the control group had a significant difference with the Lagerstroemia speciosa and aloe vera extract gel group (p-value<0.05), however, the Lagerstroemia speciosa group did not have any significant difference with the aloe vera group (0.123>0.05). Conclusion: There was no difference in the amount of FGF-2 expressions on the wound healing process of the injured palatal tissue of Sprague-Dawley rats with hyperglycemic after application of the Lagerstroemia speciosa and aloe vera extract gel.